Single aspects of job satisfaction among engineers - Vukelić, Anton (Array, 2008)
In a socio-professional group of engineers by means of a survey based research the relationship between the job satisfaction as a whole (global satisfaction) and the single aspects of satisfaction, i.e. their attitudes towards the company and work, has been analyzed. The results show that alongside with satisfaction with one's own status, with the immediate superiors and with the personal income, a crucial role in the global satisfaction is played by the degree of attachment to the company and by the impression that the most significant functions are allocated to the really most capable individuals.